Settlement of bad credit disputes on unsecured loans is reviewed from Fatwa DSN MUI NO: 19/DSN-MUI/IV/2001 in Roburan Dolok Village, South Panyabungan District Mandailing Natal District - Lubis, Nora Elviana; Sativa, Annisa (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Bad credit is a condition when the borrower or debtor can no longer continue payments or debt installments. As a result of the debtor who cannot payhis debt, his credit becomes stopped or bad. This study aims to determine the settlement of bad credit disputes on unsecured loans in terms of Fatwa DSN MUI NO: 19/DSN-MUI/IV/2001 in Roburan Dolok Village, South Panyabungan District, Mandailing Natal Regency. This research feeds empirical legal research, by describing Islamic views on bad loans and the process of handling bad loans, taking samples by conducting interviews with related parties. The final conclusion shows that the implementation of bad credit dispute resolution in Roburan Dolok Village is in accordance with DSN-MUI fatwa No. 19/DSN-MUI/IV/2001 concerning Qardh, where it is explained that if one party does not fulfill its obligations or there is a dispute between the parties, then the settlement is carried out through the Shari'ah Arbitration Board or the Religious Court after no agreement is reached through deliberation.